A Literary Review on Different Treatment Modalities in Arsha (Hemorrhoids) - Basak, Nabanita; Sharma, V D (International Research Journal of Ayurveda & Yoga, 2022)
Arsha is a very common ano-rectal disease, which destroys the patient’s life as an enemy does. In modern science, it may be co-related with haemorrhoids. Haemorrhoid is a type of ano-rectal ailment that becomes more common as people get older. According to John Goligher (1984), 50 percent of people over the age of 50 years may have haemorrhoids after a thorough examination. It doesn’t have a single cause, and it usually manifests as a group effort. In order to cure the patient, these conditions should be addressed with caution. Ayurveda and modern science have both outlined many therapies, surgical procedures, medicines etc. When treating this disease, a specific modality should be considered in each circumstance. Patients, however, receive incorrect therapies or medicines due to a lack of information, resulting in several consequences. So, using a comparison of basic concepts, the right treatment of arsha described in ayurveda and western science is elaborated here.